Vascular and metabolic effects of the haem oxygenase-1 inducer haem arginate in subjects with the metabolic syndrome: A translational cross-over study. (January 2016) - Dekker, Douwe; Dorresteijn, Mirrin J; Peters, Wilbert HM; Bilos, Albert; Pennings, Sebastiaan WC; Wagener, Frank ADTG; Smits, Paul
This translational randomized and vehicle-controlled cross-over study was performed to assess the impact of haem arginate treatment on haem oxygenase-1 induction, endothelial function and insulin sensitivity in subjects with the metabolic syndrome ( n = 14). Both treatment periods consisted of 5 days. Haem arginate or vehicle (l -arginine) was administered intravenously on Days 1 and 3. Forearm blood flow in response to acetylcholine and nitroglycerine was measured by venous occlusion plethysmography (Day 3), insulin sensitivity by a hyperinsulinaemic clamp procedure (Day 5). Haem arginate did not improve endothelial function or insulin sensitivity but significantly reduced the vasodilator response to nitroglycerine ( p < 0.01). These negative findings are in contrast to the preclinical data, which may be due to short duration of therapy and limited haem oxygenase-1 induction as well as interference by markedly elevated plasma haem levels observed after haem arginate treatment ( p < 0.01). Future studies should pay attention to the delicate balance between sufficient dosing and timely normalization of plasma haem levels.